2021
DOI: 10.1155/2021/6651045
|View full text |Cite
|
Sign up to set email alerts
|

Coinfections with Respiratory Pathogens among COVID-19 Patients in Korea

Abstract: The detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in upper and lower respiratory specimens and coinfection with other respiratory pathogens in patients with coronavirus disease 2019 (COVID-19) was investigated. Study subjects (N = 342) were retrospectively enrolled after being confirmed as SARS-CoV-2 positive, and their nasopharyngeal swab (NPS), oropharyngeal swab (OPS), and sputum specimens were restored for SARS-CoV-2 retesting and respiratory pathogen detection. The majority of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
13
2
1
Order By: Relevance
“…HBoV, an enveloped virus, was detected consistently during the COVID-19 pandemic according to the Korea Influenza and Respiratory Viruses Surveillance System [23]. The higher detection of viral pathogens in the 20-39 age group suggests that young patients with COVID-19 are more susceptible to respiratory viral coinfection, consistent with the findings of a previous study [20].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…HBoV, an enveloped virus, was detected consistently during the COVID-19 pandemic according to the Korea Influenza and Respiratory Viruses Surveillance System [23]. The higher detection of viral pathogens in the 20-39 age group suggests that young patients with COVID-19 are more susceptible to respiratory viral coinfection, consistent with the findings of a previous study [20].…”
Section: Discussionsupporting
confidence: 86%
“…HRV with a long period of viral shedding and environmental resistance [23] has been associated with higher morbidity rather than mortality, causing an economic burden [24]. HBoV was also observed in a previous study using the same RT-PCR kit in South Korea [20]. HBoV, an enveloped virus, was detected consistently during the COVID-19 pandemic according to the Korea Influenza and Respiratory Viruses Surveillance System [23].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The clinical performance of the SC2FabR assay showed 100% diagnostic accuracy, and the assay results were consistent with those of the reference platforms (2019-nCoV or Standard M assays) (Table 2). In addition, the clinical performance of the SC2FabR kit for the analysis of seasonal RVs showed 98.4-100% diagnostic accuracy (Table 2), and the simultaneous detection of co-infection with SARS-CoV-2 presented 100% reliability for Flu A and RSV (Supplementary Table S2), which is similar to the results of previous studies [28]. Thirteen samples that yielded inconsistent results frequently gave "weakly positive" reactions in the SC2FabR assay, with the target amplification detected in the "gray" region [29], with Ct values of 36 to 40 (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 85%
“…Abbas et al (Abbasi et al, 2021) has made a serendipitous observation that non-invasive ventilation improved the survival of mice with bacterial pneumonia and the improved survival is associated with the expression of surfactant protein A. Majority of the COVID-19 patients are also reported to be co-infect with other pathogens (Hughes et al, 2020;Jiang et al, 2020;Kim et al, 2020;Roh et al, 2021) and many research papers (Floros and Phelps, 2020;Tekos et al, 2020;Xu et al, 2020) have highlighted that SP-A variants have shown beneficial effects in the treatment of ARDS in COVID-19 patients under different scenarios. Thus, in an opinion article by Abbs et al (Abbasi et al, 2021), the team has expressed that non-invasive ventilation using high-flow nasal cannula (HFNC) may be beneficial for COVID-19 patients which Oxygen in the alveolus is exchanged with carbon dioxide in the capillaries.…”
Section: Pulmonary Surfactants In Covid-19mentioning
confidence: 99%